Tafsir Ilmi in Indonesia: History, Paradigm and Dynamic Interpretation - Rizki Firmansyah (Universitas Ahmad Dahlan, 2021)
Interpretation writing in Indonesia has been going on long enough. First appeared in sixteenth Century. A quiver of Indonesian interpretations after grows more and more. The motifs of interpretaation varied. Scientific interpretation is the one who took a role in this and it is said to have emerged in the 1980s to date. During that time, many of ilmi's interpretation have appeared in Indonesia. The Study attempts to unravel the history of ilmi's interpretation, paradim and ITS dynamic. The method used is a descriptive method with qualitative approach by restricting the focus of the work to ilmi's interpretation in Indonesia. The result of this Study suggest that Ilmi interpretation in Indonesia is dynamic and veried and is experincing promising development.